Impulsivity, Dark Triad and Moral Disengagement among Clinical Psychologists - Zeenat; Sidra Tanvir; Hamra Zaheer; Bismillah koasar; Abdul Aziz (Dialogue Social Science Review (DSSR), 2025)
This research paper investigated the influence of impulsivity, Dark Triad personality attributes (narcissism, Machiavellianism, and psychopathy), and moral disengagement in Pakistan among 120 licensed clinical psychologists (60 male, 60 female) of age 25 to 55 years. Based on the standardized instruments Barratt Impulsiveness Scale, Dirty Dozen Dark Triad Scale and Bandura Moral Disengagement Scale the study was able to use Pearson correlation and hierarchical regression as an analysis. The results indicated that impulsivity and moral disengagement were significantly and positively related as were Dark Triad traits and moral disengagement. The strongest predictor included psychopathy, narcissism and impulsivity. The research made another important note in that the high levels of the element of impulsivity, as well as the traits included in the Dark Triad, were found to be contributing to the moral disengagement particularly in ethically stressful situations. The outcomes highlight the role of emotion management, ethical conduct and personality evaluation in training and professional growth of clinical psychologists as the means of maintaining ethical principles and enhancing therapeutic alliance. Keyword: Clinical Psychologists, Impulsivity, Dark Triad, Moral Disengagement, Personality Traits.